The effect of classroom activities strategy of the expressive performance on Fourth-grade primary school pupils. (Journal of the College of Basic Education, 2022)
the aim of the current research is to find out ( the impact of the classroom activity strategy in the expressive performance to elementary students /girls/ fourth grade ). Therefore, the researcher assumed the following zero hypothesis. There are no statistically significant differences at level ( 0,05) between the average scores of female pupils experimental group studying the expression subject in accordance with the classroom activity strategy, and the average scores of the normal students group studying the same subject in the normal manner in series remote tests.The research sample consisted of 64 female pupils from the fourth grade primary school of the (suburban school). In the governorate of Diyala, Baquba center, primary school was distributed to two experimental groups, one of which consisted of 32students who studied the substance of expression according to the strategy of activities in class, and other students normal group have been formed of 32 student ,also studied the same substance in the normal manner. The researcher studied both parties of research by herself.The researcher performed equivalence between the two research groups on the following variables :(lifetime calculated In months, Arabic degrees for half the year, and parents' educational attainment). the researcher Prepared Five sequential remote tests based on ready-made correction tests and when data are collected Their statistical analysis using the second test for two independent samples . The research result showed the superiority of the experimental group to the normal group of students in sequential remote test.The researcher reached a number of conclusions, including :- 1- the use of the classroom activity strategy in teaching of expression provides female students with a better linguistic wealth.2_ The use of the method of applying classroom activities helped to attract the attention of female students to the lesson. The researcher reached a number of recommendations, including:The introduction of classroom activities in teaching is considered a proven method for the performance of female pupils. (2) the need to set up training courses for teachers to teach in modern teaching methods.. A number of Suggestions have also been made:(1) conducting a study similar to the current study at other levels of schooling.Conducting of a similar study in other subjects.